Pair - Atomic effect in the micromaser: Narrowing of the linewidth - G, Ariunbold; Ts, Gantsog (Scientific transaction of the National University of Mongolia. Physics, 2022)
An average HamiItonian, which contains pair-atomic effects, is used to develop a theory of the micromaser. A modified master equation is derived and both a steady-state and a time-dependent solutions are found showing that, the trapping conditions are disturbed by influence of two atomic events. An approximate as well as an exact spectrum are calculated and narrowing of linewidth is demonstrated within the framework of presented theory.